Associations among Personality, Satisfaction, and Maxillary Incisors Shape: A Cross-Sectional Study - Sândyla Prata Paixão; Djamily Biz; Beatriz Alvares Cabral de Barros; Renata Gondo; Sylvio Monteiro Júnior (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To investigate the association between satisfaction with maxillary incisors’ shape and personality types determined through a physiological instrument and the association between tooth shape preferred by patients and tooth morphology determined by dentists. Material and Methods: Thirty-nine male and 85 female patients answered a 3-stage questionnaire to determine their personality (Enneagram Test), satisfaction with incisors’ shape, and preferred shape for maxillary teeth. Six experienced dentists independently evaluated photographs of the patients to determine their incisor’s morphology. The associations among variables were analyzed using the Chi-square test (p<0.05). Results: The associations between personality types and tooth shapes preferred by patients (p=0.642) or tooth morphologies determined by the dentists were not significant (p=0.096). A total of 96 (77.4%) and 28 (22.6%) patients were respectively satisfied and dissatisfied with their maxillary incisors’ shape. A significant association was observed between satisfied patients (36) who preferred a tooth shape that matched their tooth morphologies determined by dentists (p=0.028); however, the association between dissatisfied patients (7) who preferred a tooth shape that matched their tooth morphologies determined by dentists was not significant (p=0.391). Conclusion: The patient’s personality does not seem to influence his/her own or the dentist’s perception of tooth morphology. Considering distinctive perceptions of incisors’ shape that may lead to different expectations, patients and dentists must corroborate during dental esthetic planning.